Eco-tourism Development Strategy Based on Local Potential in the Forest of Akebalanda Village, Moya Village, Ternate City - Mahdi Tamrin; Abdul Kadir Kamaluddin (TECHNO: JURNAL PENELITIAN, 2021)
The concept of eco-tourism connects nature tourism trips that have a conservation mission that is carried out simultaneously with forestry development in forest areas that is applied to social forestry schemes. The scheme focuses more on empowerment in a participatory manner to increase the community's ability to manage the potential of forest resources in the vicinity. The purpose of this study; 1) Knowing the potential of Akebalanda Village Forest in Moya Village, 2) Develop a strategy for the development of Forest Eco-tourism in Ake Balanda Village, Moya Village. The method in this study is to observe and inventory the potential of vegetation. Field observations were carried out to determine the location of data collection and obtain actual data regarding the potential of village forests and the eco-tourism development strategies used, and continued with structured interviews with group administrators and related parties, then the data will be analyzed using SWOT analysis. The results showed that the flora potential in the eco-tourism area of Gamalama Forest, Akebalanda Village in Moya Village, was very diverse. This is indicated by the discovery of 31 types of plants developed in the area. In addition to the potential of flora, there is also another potential as an attraction for the development of Gamalama Eco-tourism, namely natural potential. Based on the calculation of scores on the EFAS and IFAS matrices, the Gamalama ecotourism development in the forest of Akebalanda village is in quadrant I (0,16 – 0,94). Quadrant I is a very favorable situation in doing business. This position has opportunities and strengths from two factors, namely internal factors and external factors that can be utilized by KUPS and LPHD. The strategy that must be applied in this condition is to support an aggressive growth policy (Growth Oriental Strategy).